Pelatihan Pembuatan Yoghurt bagi Guru dan Siswa SDN 01 Wonorejo Singosari Malang - Ma'arif, A. Samsul; Majid, Alima Fadhila (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
Yogurt is a dairy product that undergoes fermentation using Lactobacillus bulgaricus and Streptococcus thermophilus bacteria. Yogurt is good for digestion which can reduce toxic substances in the body. The purpose of the service activity is to increase the consumption of cow's milk in the form of yogurt, especially in Wonorejo Village. The community service method is carried out face to face which will be held on January 20-21 2023, at SDN 01 Wonorejo. The implementation of this service activity is by demonstrating in the practice of making yogurt. The results of this service are in the form of increased knowledge and understanding of students, SDN 01 Wonorejo teachers and the community in Wonorejo Village, Singosari District in designing and making processed dairy products, as well as community skills in making yogurt.